(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2010)
The micellar extraction of the aluminium and ferrum complexes with the phase formation induced addition by micellar phases of the non-ionic surfactants OP-10 and Triton X-100 was investigated. The influence of the concentration conditions, cationic surfactant and phenol on the phase separation parameter of aluminium and ferrum was established.